1999
DOI: 10.1093/oxfordjournals.molbev.a026057
|View full text |Cite
|
Sign up to set email alerts
|

Positive selection on the H3 hemagglutinin gene of human influenza virus A

Abstract: The hemagglutinin (HA) gene of influenza viruses encodes the major surface antigen against which neutralizing antibodies are produced during infection or vaccination. We examined temporal variation in the HA1 domain of HA genes of human influenza A (H3N2) viruses in order to identify positively selected codons. Positive selection is defined for our purposes as a significant excess of nonsilent over silent nucleotide substitutions. If past mutations at positively selected codons conferred a selective advantage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
261
2
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 338 publications
(286 citation statements)
references
References 23 publications
17
261
2
2
Order By: Relevance
“…Our approach, however, is general. As is customary, we restrict attention to the hemagglutinin protein, against which neutralizing antibodies are generated [14]. Shown in figure 1 is the hemagglutinin protein for the A/Fujian/411/2002 strain with the epitope regions highlighted.…”
Section: Methodsmentioning
confidence: 99%
“…Our approach, however, is general. As is customary, we restrict attention to the hemagglutinin protein, against which neutralizing antibodies are generated [14]. Shown in figure 1 is the hemagglutinin protein for the A/Fujian/411/2002 strain with the epitope regions highlighted.…”
Section: Methodsmentioning
confidence: 99%
“…Such studies reveal that modifications to HA1, the immunogenic part of HA, accrue at a dramatic rate. Those sites of HA1 involved in antigen determination exhibit significantly more non-synonymous nucleotide substitutions than synonymous substitutions (6,7), whereas the remaining sites show the more common pattern of primarily synonymous variation. These observations demonstrate that HA is undergoing positive Darwinian selection for new antigenic variants (8).…”
mentioning
confidence: 96%
“…Recent studies revealed that there was considerable heterogeneity in substitution rate among amino acid positions (32,69). These facts suggest that an analysis of variation at the single-amino-acid-site level would be very important to understanding the nature of variations and elucidating the evolutionary mechanism (5,16,21,44). Recently, methods to detect selection at the single-site level by comparison of synonymous and nonsynonymous substitutions have been developed (44,57), and these methods were applied to the sequences of HIV-1, including the V3 region, which were periodically sampled from individual patients (22).…”
mentioning
confidence: 99%